Zionism : A Very Short Introduction - Stanislawski, Michael, 1952- (New York Oxford University Press, 2017)
"This Very Short Introduction discloses a history of Zionism from the origins of modern Jewish nationalism in the 1870's to the present. Michael Stanislawski provides a lucid and detached analysis of Zionism, focusing on its internal intellectual and ideological developments and divides"
Include Illustrations and Index
Keywords: HISTORY -- Jewish. -- modern Jewish nationalism -- Zionism -- History. -- Israel, ...